2008
DOI: 10.1556/avet.56.2008.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serological evidence of Anaplasma phagocytophilum infection of farm animals in the Black Sea Region of Turkey

Abstract: This study was designed to determine the presence and the prevalence of Anaplasma phagocytophilum infection in sheep and cattle in the Middle and Eastern Black Sea Regions of Turkey in which the potential vector, Ixodes ricinus, is widespread. Blood samples were collected from 720 sheep and 720 cattle from 6 provinces of the region, and used for detecting antibodies to A. phagocytophilum by indirect immunofluorescent antibody test (IFAT) and specific nucleic acids by a nested polymerase chain reaction (PCR). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 43 publications
(79 reference statements)
0
25
2
1
Order By: Relevance
“…Anaplasma is globally the most prevalent tick-borne pathogen of cattle and has a worldwide distribution with regions of endemicity on six continents (Futse et al, 2003) and high incidence in tropical and subtropical regions of the world (De La Fuente et al, 2005;Torina et al, 2008;Gokce et al, 2008;Ooshiro et al, 2009;Ruybal et al, 2009). A. centrale is widely distributed but has never been reported in North Africa, it has been reported only in South Africa (OIE, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Anaplasma is globally the most prevalent tick-borne pathogen of cattle and has a worldwide distribution with regions of endemicity on six continents (Futse et al, 2003) and high incidence in tropical and subtropical regions of the world (De La Fuente et al, 2005;Torina et al, 2008;Gokce et al, 2008;Ooshiro et al, 2009;Ruybal et al, 2009). A. centrale is widely distributed but has never been reported in North Africa, it has been reported only in South Africa (OIE, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A few previous serological studies involving A. marginale reported that the sero-prevalence ranged from 14.86% to 59.3% in different regions of Turkey [3,9,10,12] . The differences between infection prevalence may be attributed to the changes in climatic condition, intensity of tick infestation, and also contaminated needles and instruments transmission is an efficient way of infection spreading in herds [23] .…”
Section: Discussionmentioning
confidence: 96%
“…is found to be major transmitting agent [2,7,8] . Although there are some prevalence reports of anaplasmosis in cattle with high rate (up to 80%) [1,3,[9][10][11] , information about prevalence rates in small ruminants is restricted in Turkey [12,13] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations